Endeavour : series 1 - Evans, Shaun, 1980-; Allam, Roger; Lesser, Anton; McCarthy, Colm, 1973-; Dexter, Colin ([Alexandria, Va.] : PBS Distribution, 2013)
Detective Constable Endeavour Morse becomes drawn into a murder investigation that changes the course of his life.
Disc : Pilot -- Girl ; Disc 2: Fugue -- Rocket ; Disc 3: Home.
Based on the novels by Colin Dexter.
Shaun Evans, Roger Allam, Anton Lesser, Sean Rigby, Jack Laskey.
Originally broadcast as segments of the "Masterpiece mystery!" series of "Masterpiece theatre" 2012-2013.
Rated: TV-14; for violence, sexuality and disturbing images.
DVDs, Dolby digital stereo, widescreen.
Closed-captioned.
Keywords: Morse, -- Inspector (Fictitious character) -- Fiction; Morse, -- Inspector (Fictitious character); Detective and mystery stories; Criminal investigation -- England -- Oxford -- Fiction; Detective and mystery television programs; Television programs; Criminal investigation; Detective and mystery stories; Detective and mystery television programs; Television programs; Oxford (England) -- Fiction; England -- Oxford; Fiction